A Fully-Immersive and Automated Virtual Reality System to Assess the Six Domains of Cognition: Protocol for a Feasibility Study - Lim, Jie En; Wong, Wei Teen; Teh, Tuan Ann; Lim, Soon Huat; Allen, John Carson; Quah, Joanne Hui Min; Malhotra, Rahul; Tan, Ngiap Chuan (Frontiers in Aging Neuroscience, 2021)
Introduction Dementia is increasing in prevalence in aging populations. Current questionnaire-based cognitive assessments may not comprehensively assess cognitive function and real-time task-performance. Virtual reality (VR) technology has been used in cognitive assessments but existing systems have limited scope in evaluating all cognitive domains. We have developed a novel, fully-immersive VR system (CAVIRE: Cognitive Assessment by VIrtual REality), which incorporates automated audio-visual instructions. An automated scoring matrix to assess the six cognitive domains – perceptual-motor function, executive function, complex attention, social cognition, learning and memory, and language – is embedded in the CAVIRE system. Aims The primary aim is to evaluate the feasibility of using the CAVIRE system to assess cognitive function of participants across different age groups from 35 to 84 years old. The secondary aims are to determine the CAVIRE performance-indices (completion time and scores) of the participants and to assess their acceptability towards the use of CAVIRE as a modality for cognitive assessment. Methods 175 participants will be assessed by CAVIRE at a primary care clinic in Singapore. They will be first assessed using questionnaires: Montreal Cognitive Assessment (MoCA), Abbreviated Mental Test (AMT), Mini-Mental State Examination (MMSE), Basic Activities of Daily Living (BADLs), Instrumental Activities of Daily Living (IADLs). Those aged 65-84 years will be grouped into cognitively-intact (n=50, MoCA score>26) and cognitively-impaired (n=50, MoCA<26). The CAVIRE performance-indices of cognitively-healthy younger participants aged 35-64 years (n=75) will serve as benchmark references. CAVIRE auto-computes the participant’s performance-indices in 13 different segments. The tasks include domestic chores, memory, shopping and social interactions. The proportion of participants who complete the entire VR assessment in each age group will be evaluated as feasibility indicators. The CAVIRE performance-indices will be compared across the different age groups. Feedback on the acceptability of the CAVIRE system will be collated and compared among the participants across the age groups. Significance CAVIRE is designed to assess the six domains of cognitive function using VR. The results of this feasibility study will provide insights for the implementation of the CAVIRE system as an alternative modality of cognitive assessment in the community.